Algonquin materials, Selected materials, 1676-1930, on Indian linguistics - Vaultier, Peter; Crespieul, François de, 1639-1702; Cuoq, J. A. (Jean André), 1821-1898; Laure, Pierre-Michel, 1688-1738 (1637)
Part of a collection comprised of religious and linguistic materials in various Native American languages. Many were written by Jesuit missionaries of New France, although Cuoq was Sulpician. These eight items primarly concern the Algonquin language and include linguistic and religious materials in French, Latin, and Algonquin such as prayers, hymns, canticles, music, catechisms, etc. A few items incorporate some Abenaki, Inuit, and Innu language material as well. There is also the 125-page Registre de Sillery 1637 a 1690 containing Native baptismal and confirmation records. Originals in the archives of the Séminaire de Québec at the Université Laval [formerly the Séminaire de Québec] and the Archives de l'Archeveche de Quebec.